DIPLOMASI BILATERAL PENYELESAIAN SENGKETA PERBATASAN INDONESIA-MALAYSIA (Studi Kasus Camar Bulan, Kabupaten Sambas, Kalimantan Barat) - Putranto, Fajar Tri (Transformasi, 2015)
Background of this dispute is the annexation of territory taken by the Malaysian in Camar Bulan region in 2011-2012. This is done by the Malaysian because based on the covenant in Kinabalu (1975) and in Semarang (1978) in which the Malaysian side to enter the territory Camar Bulan as Outstanding Boundary Problem (OBP) region of Sarawak, Malaysia. Of the dispute, a peaceful solution chosen by both parties. Peaceful settlement made by Indonesia through bilateral diplomacy. In bilateral diplomacy, the Indonesian government talks and negotiation of ministerial talks to the head of state-level negotiations. The problem of this research is how the bilateral diplomacy role in resolving disputes that occurred in the border areas of Indonesia and Malaysia, precisely in Camar Bulan, Sambas, West Kalimantan. Methods and research techniques used in this research is the method kualitatif and data collection techniques through the study of literature. Based on the framework and approach system is used, resulting in an image that is that the border dispute that occurred in Camar Bulan occur because of the actions of Malaysia who claim unilaterally on an area of 1,400 hectares belonging to Indonesia and bilateral diplomatic action as the action taken by the Indonesian government in resolving disputes tersebut.Dari frontier research results concluded that bilateral diplomacy Indonesia still has not managed to do this because there is found a bright spot in the settlement of disputes in Camar BulanKeywords: Camar Bulan, Border Dispute, Bilateral Diplomacy